Measuring the discourse - Sauer Bredvik, Linda (Journal of Interreligious Studies, 2021)
The aim of this article is to demonstrate how an emergent mixed methods analytical framework can be used to identify and understand multifaith speakers’ use of metalinguistic indicators (or signs) in interreligious dialogues and how patterns of use of these signs can affect the conduct and outcome of the dialogue. The article also provides applied approaches for communicatively effective conversations between peoples of different faith practices.